The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1097/mop.0000000000001234
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric musculoskeletal infections

Abstract: Purpose of reviewThe aim of this article is to review the recent guidelines and literature regarding the diagnosis and the treatment of common pediatric musculoskeletal infections: septic arthritis, osteomyelitis, pyomyositis, and Lyme disease.Recent findingsIn the last decade, a better understanding of the causative organisms of common bacterial infections, including Kingella, leads to prompt targeted antimicrobial coverage in all musculoskeletal infections. Prompt diagnosis and treatment continues to be the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…This is especially crucial when a patient is clinically deteriorating and/or there is concern for a septic joint. MRI is a powerful tool with high sensitivity and specificity for diagnosing osteomyelitis and septic arthritis [ 13 , 14 ]. Ultrasonography is another option to evaluate for a joint effusion and is an important tool in the workup of these patients, but MRI has higher sensitivity and specificity as well as increased interobserver reliability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially crucial when a patient is clinically deteriorating and/or there is concern for a septic joint. MRI is a powerful tool with high sensitivity and specificity for diagnosing osteomyelitis and septic arthritis [ 13 , 14 ]. Ultrasonography is another option to evaluate for a joint effusion and is an important tool in the workup of these patients, but MRI has higher sensitivity and specificity as well as increased interobserver reliability.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study of 93 patients demonstrated a reduction in unplanned returns to the operating room from 50% to less than 27% after implementing new guidelines that mandated preoperative MRIs for all pediatric patients with suspected periarticular infections [ 17 ]. The downsides to preoperative MRI include its high costs and the additional time necessary to use the technique at most hospitals, especially when anesthesia is necessary [ 13 , 14 ]. Even with the extensive resources present at the pediatric tertiary referral centers included in this study, patients who underwent preoperative MRI experienced significantly greater time to surgery in both the main cohort and septic joint subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, early diagnosis of PSA is important, as it may guide appropriate antibiotic administration and intravenous fluid resuscitation prior to surgical intervention ( 31 ). CAR upon admission could guide preoperative antibiotic selection, with the best cut-off point of CAR being 0.447.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by defining the anatomical and spatial extent of the infection, MRI provides orthopedic surgeons with some of the most precious information to establish the surgical indication, confirm the indication to arthrocenthesis or surgical drainage and finally plan the surgery. MRI for pediatric musculoskeletal infections has a sensitivity of 81%–100% and specificity 67%–94% compared to CT scan (sensitivity of 67%–100% and specificity 50%) ( 18 , 19 ). MRI allows the visualization of bone marrow oedema, indicating bone abscess formation, and extraosseous spread of the infection.…”
Section: Towards Systematic Use Of Mrimentioning
confidence: 99%
“…Multiple institutional guidelines have demonstrated that its earlier use remarkably improves the identification of OAIs surgical candidates, thus reducing the rate of sequelae and reoperations ( 1 , 5 , 6 , 12 16 , 20 24 ). Despite its benefits, the awareness of the resource intensity required by MRI has led to the development of multidisciplinary teams, to expedite the discussion around OAIs management among all the implicated stakeholders, such as pediatricians, orthopedic surgeons, anesthesiologists and radiologists ( 15 , 16 , 18 , 20 , 24 26 ). When facing OAIs these different specialists might not share the same definition of emergency, with consequent dissent about the diagnostic and therapeutic strategy.…”
Section: The Difficulty Of Accessing An Emergency Mrimentioning
confidence: 99%